The myth of corporate art: the start of the Peter Stuyvesant Collection and its alignment with public arts policy in the Netherlands, 1950–1960. Issue 3 (16th April 2021) - Witte, Arnold
ABSTRACT: The Dutch Peter Stuyvesant art collection, started in 1960, seems to offer the archetypical success story of a private entrepreneur sharing his love of art with his employees. Yet this specific corporate art collection was not the brainchild of an enlightened director, but was initiated by two private foundations functioning as semi-governmental institutions that had been promoting art and culture amongst the Dutch working classes since 1950. The historical sources on this initiative also indicate that after 1945 corporate art collections were intended as an alternative way of implementing the arm's-length principle in Dutch cultural policy. This case study, and similar international examples, shows that first, corporate art collections should be explained within the broader political and cultural context, and that second, research on the history of cultural dissemination should include the private actors that aligned their goals with government policies towards the arts.